Students’ Perspectives on Academic Mentorship Program for Undergraduate Medical Education - Purnajati, Oscar Gilang; Hapsari, Saverina Nungky Dian (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Academic mentors are needed to help students start and develop some parts of professional competence that may be hidden in medical education programs and constantly evolving over time. Academic mentorship model research has been developed in the context of medical education in European and North American countries, which have different cultural contexts from Eastern countries. Therefore, students’ perspective for the model of valued academic mentorship in this context needs to be explored further to become a recommendation for faculties in providing academic mentorship to students. The study aimed to explore how undergraduate medical students perceive the valuable academic mentoring model.Methods: This study used qualitative approach. Seventeen medical students of Universitas Kristen Duta Wacana (UKDW) from year 2018-2021 were divided into 2 focus group discussions. Thematic analysis was applied to analyse the findings. Results: The FGD raised the themes of students' perspectives on valuable academic mentorship if there is a good mentors-students relationship, providing support, hope and role models, flexibility, and effectiveness of academic mentorship, as well as students' hopes for academic mentorship in the future.Conclusion: Academic mentorship is a guidance that provides hope and support according to student needs. The models of valuable academic mentorship according to students is if there is flexibility in mentoring time and effective communication. Future mentoring models should describe future career opportunities and professionalism as a doctor.